FRI0395 Low-Dose Semi-Coronal CT of The Sacroiliac Joints in The Early Diagnosis of Ankylosing Spondylitis. (15th July 2016) - Gao, D.; Li, K.; Wang, Y.; Wen, Q.; Zhu, J.; Zhang, J.; Huang, F.
Abstract : Background: Imaging modalities are essential for the diagnosis of ankylosing spondylitis (AS). Radiographic sacroiliitis is the requirement of 1984 modified New York (mNY) criteria for AS but with the disadvantage of low sensitivity. MRI has the advantage of detecting active inflammatory lesions but was criticized for low specificity. Computerized tomography (CT) has higher diagnostic accuracy than radiography in detecting structural changes, but its application has been limited for high radiation dose. The reduction of radiation dose can be achieved by decreasing the tube current [1] and previous study has demonstrated that effective dose (ED) of semi-coronal sacroiliac joint (SIJ) CT is at least six times lower in female or nearly four times lower in male than that of axial SIJ CT [2] . Objectives: To evaluate the value of low-dose semi-coronal SIJ CT in the early diagnosis of AS. Methods: Thirty-three patients diagnosed by mNY criteria who had pre-existing axial SIJ CT in past two years with visible structural damage were enrolled. These patients underwent low-dose semi-coronal SIJ CT examination which was obtained at 3-mm slices, 140 kV and 120 mAs, with the gantry tilted 20–25° cranially. The ED of the low-dose semi-coronal CT and the pre-existing conventional axial CT were compared. Image qualities of the low-dose semi-coronal CT were blind-graded separately by 2 rheumatologists into poor, fair, good or excellent. And the correlation between image quality and body mass index (BMI) was analyzed. The CT scans were read in a blinded manner by 2 rheumatologists who had been trained by radiologists. CT scans of the two groups were graded respectively by mNY criteria, the criteria established by Lee [3] and the Innsbruck criteria [4] . The kappa coefficient was used to assess the consistency of grading between the two groups. Results: Thirty-three patients received low-dose semi-coronal CT examination with an average ED of 3.37 mSv, which meant a 49% reduction in radiation compared to the pre-existing CT. The quality of images of male patients with BMI<25 kg/m 2 and all female patients were good or excellent. Image qualities were assessed as poor or fair in 58% (7/12) male patients whose BMI>25 kg/m 2 . There was a significant negative correlation between image quality and BMI (r=-0.784, P =0.000). The grading of low-dose semi-coronal CT showed no differences as compared with the pre-existing CT by mNY criteria (see below). For the other two classification criteria, the consistency of grading between the two groups were satisfactory (kappa=0.897 by Lee criteria; kappa=0.814 by Innsbruck criteria; P >0.05). Conclusions: The radiation dose of low-dose semi-coronal SIJ CT was reduced significantly compared with the conventional axial SIJ CT with acceptable diagnostic efficacy. References: Gurung J, et al. Multislice CT of the pelvis: dose reduction with regard to image quality using 16-row CT. Eur Radiol. 2005;15:1898–905. Jurik AG, et al. Effective radiation dose from semicoronal CT of the sacroiliac joints in comparison with axial CT and conventional radiography. Eur Radiol. 2002;12:2820–5. Lee YH, et al. Value of multidetector computed tomography for the radiologic grading of sacroiliitis in ankylosing spondylitis. Rheumatol Int. 2013;33:1005–11. Klauser A, et al. Workshop report: clinical diagnosis and imaging of sacroiliitis, Innsbruck, Austria, October 9, 2003. J Rheumatol. 2004;31:2041–7. Disclosure of Interest: None declared